Iso-peristaltic colonic loop interposition for the treatment of benign oesophageal stricture: a case report with review of literature - Balineni, Pradeep; Kumar C., Venkata Pavan; E., Debaraju Reddy (International Surgery Journal, 2020)
Corrosive oesophageal strictures are a common and debilitating condition in India. Patients generally have dysphagia, cachexia, drooling of saliva, aspiration pneumonitis, and lung abscess. Though endoscopic dilatations are done in cases of short segment strictures, surgical oesophageal by pass is the permanent solution for this condition. A 24 years female presented with complaints of dysphagia and cachexia, due to corrosive stricture. Patient had a history of poison ingestion 2 years back. Intra-operatively stricturous mucosa is excised and an iso peristaltic colonic loop by pass was carried out. Post operatively patient had a complication of anastomotic leak which was treated conservatively, excepting which patient is symptom free and gaining weight on a follow up period of 1 year. Ever since first described by Kelling and Vuillet in 1911 colonic interposition is mostly used around the globe for oesophageal bypass in both benign and malignant conditions. Stomach and jejunum are the other conduits that can be used. Iso peristaltic loop is mostly used to reduce the incidence of reflux. Right colon or transverse colon graft based on the mid colic artery or the left colic artery owing to the reliable blood supply and less diameter. This procedure has a high complication rate of around 27% most of which are due to the vascular comprise of the graft.